Plagio e commercio nelle guide tardocinquecentesche dedicate a Napoli e Pozzuoli - Hendrix, Harald (Incontri. Rivista europea di studi italiani, 2014)
Plagiarism and commerce in late sixteenth-century guides to the city of Naples and its districtThis essay illustrates how strongly chorographical texts depend on intertextual borrowings from previous materials, up to the point of becoming a patchwork of quotations from earlier texts. It highlights how this characteristic feature of chorography becomes the object of an unusually early debate on plagiarism. This polemic between two clearly competing Neapolitan intellectuals, Tomaso Costo and Scipione Mazzella, denotes how in the 1590s the status of chorography was changing considerably. Hendrix argues that the growing numbers of visitors to a city like Naples, particularly those coming from far away, lured publishers and authors alike as of the 1580s to transform conventional chorography conceived in a context of local pride into a commercially attractive product targeting this new audience. This went along with a re-framing of existing chorographical materials, not only causing concern with regard to its dubious status oscillating between intertextuality and plagiarism, but also in view of the urban identity presented no longer to wellinformed citizens but rather now to foreign visitors much more dependent on the accuracy and reliability of the given information.